Short Communication: Evaluation of F6 generation of upland rice promising lines for drought stress tolerance (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mustikarini ED, Lestari T, Santi R, Prayoga GI, Cahya Z. 2022. Short Communication: Evaluation of F6 generation of upland rice promising lines for drought stress tolerance. Biodiversitas 23: 3401-3406. Water is important in metabolic processes affecting rice crop growth and development. Drought stress can decrease rice production, necessitating the development ofdrought-tolerant varieties. Selection of drought-tolerant can be done during the critical period plant booting phase. Thisresearch aimed to determine promising linesof upland rice tolerant to drought stress. This research was conducted from December 2019 toMay 2020 at the experimental farmofthe Faculty of Agriculture, Fisheries and Biology, Universitas Bangka Belitung. The research was laid out in a completely randomized design with a single-factortreatment. The treatment was rice genotypes consisting of 10 lines and 2 checkvarieties; each was 3 replicates. The results showed that the droughtstressin the plant booting phase of rice plants significantly affected the plant heigh character of the plant, grains number per panicle, the weight of grain per panicle, the age of flowering, and harvest time, but gave no significant effect on the number of leaves, the number of productive tillers, roots length. The upland rice lines 23A-56-30-25-1, 23A-56-30-25-12, and 23A-56-30-25-13 showed good drought stress tolerance based on leaf rolling, leaf drying, crop yield, and plant growth percentage.
Keywords: drought stress, line, plant booting phase, tolerant, upland rice